The potential role of agroforestry in ACP countries - Beets, Willem C. (Wageningen, Netherlands : Technical Centre for Agricultural and Rural Co-operation, 1989)
The general report consists of two parts: Part 1 gives a general introduction to agroforestry. In part 2 the ACP countries are classified into six ecological/ geographical zones, and a series of tables summarized the characteristics of woody plants that could be used in agroforestry programmes and outlines aspects of agroforestry in these zones
osc 31/01/2019
Loans
Keywords: Agroforestry; Agroforestry; Agroforestry